2020
DOI: 10.1016/j.mtbio.2020.100081
|View full text |Cite
|
Sign up to set email alerts
|

A novel tropoelastin-based resorbable surgical mesh for pelvic organ prolapse repair

Abstract: Pelvic organ prolapse is a common condition that affects 1 in 4 women across all age groups. It is mainly caused by vaginal birth injury and can be exacerbated by obesity and increased age. Until recently, treatment strategies often used non-degradable synthetic meshes for reconstructive surgery. However, owing to their frequent, unacceptable rate of adverse events such as mesh erosion, transvaginal meshes have been banned in many countries. Recent reports have highlighted the urgent need for biocompatible des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…To assess the possibilities, future studies should focus on the long-term host response to P4HB in larger animal models, e.g. sheep [ [56] , [57] , [58] ], including the effect of mesh degradation and mechanical properties. Finally, as bacterial contamination significantly affects the host response, we would recommend future studies to take into account the effect of the vaginal microflora on mesh acceptance and integration.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the possibilities, future studies should focus on the long-term host response to P4HB in larger animal models, e.g. sheep [ [56] , [57] , [58] ], including the effect of mesh degradation and mechanical properties. Finally, as bacterial contamination significantly affects the host response, we would recommend future studies to take into account the effect of the vaginal microflora on mesh acceptance and integration.…”
Section: Discussionmentioning
confidence: 99%
“…The key to safe and efficacious TE in PFDs was the generation of some tissue substitute by materials with nano-architecture/nanofiber technology [163] or 3D printing, mimicking EMC pelvic floor topography, mainly vaginal EMC, or to induce favorable tissue mechanical responses, or to add some EMC constituents (as tropoelastin-the elastin core in EMC network, besides collagen, lost in POP) [164], for production of mesh/scaffold new generation, which allows entrapment, and persistence of seeded eMSCs/MenSCs up to 14 days after implant [41]. eMSCs are in vitro optimized in serum free conditions-fibronectine is the optimal substrate for human eMSCs attachment [91], and eMSCs transcriptome reveals improved potential for cell based therapy after adding TGF-β receptor inhibitor in culture medium (to prolong their undifferentiated status after implantation, by eMSCs apoptosis, and senescence prevention, and maintaining the percentage of SUSD2 + cells to more than 90% for all samples) [165].…”
Section: Tissue Engineering With Endometrial and Menstrual Mesenchyma...mentioning
confidence: 99%
“…However, due to the degradation rate of the electrospun biodegradable ureidopyrimidinone-polycarbonate mesh, the authors concluded that the Restorelle® and electrospun non-degradable polyurethane meshes were most suitable for further investigation Aghei-Ghareh-Bolagh et al reported manufacture of multimeter electrospun fibrous yarns based on tropoelastin/PCL mixtures (Fig. 9E-H) (Aghaei-Ghareh-Bolagh et al, 2020).. Tropoelastin is the monomer subunit of elastin, a component of the extracellular matrix, which is known to support cellular growth. Yarns containing 1:1 ratio of tropoelastin and PCL were degradable and supported cellular growth.…”
Section: Electrospun Meshes For Vaginal Graftingmentioning
confidence: 99%